Sistem Pendeteksi Kebocoran LPG Berbasis IoT Menggunakan Metode Fuzzy Logic Mamdani dengan Integrasi Aplikasi Blynk - Mahitala, Zadan Fairuz; Ryansyah, Eddy; Permana, Andari Yasinta; Susilawati, Susilawati (LPPM Universitas Dinamika Bangsa, 2025)
Cooking activities are part of the daily routine, especially for housewives. However, incidents of kitchen fires frequently occur due to forgotten actions such as falling to turn off the stove or undetected leaks in Liquified Petroleum Gas (LPG) systems. This project aims to provide an early warning system to prevent LPG gas leaks in residental areas, particularly where public awareness and timely detection are still lacking. The proposed device integrates Internet of Things (IoT) technology to enable real-time monitoring. The methodology employed in this study utilizes a mamdany fuzzy logic algorithm, in which the degree of truth is determined based on weighted values. This research is expected to contribute in public knowledge and serve as a preventive measure of households in anticipating gas leak-induced fires. Additionally, the system aims to support firefighters and family members by providing an efficient early warning mechanism.